The role of South Africa's Universities and higher education in entrepreneurship development - Malatjie, I. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
South Africa is characterised by high unemployment over the recent years. Major concern is the youth unemployment rate that continued to rise to 56.4% in 2019 from 55.2% in the prior period and of which graduate unemployment is particularly higher. Lack of work experience and entrepreneurial skills contributes to this challenge. Thus entrepreneurship has been recognised as one of the tools that drives the economy of a country and entrepreneurial activities are not only the incubator of technological innovation, but they also provide employment opportunities and increase competitiveness. Entrepreneurship is pivotal to the growth of the South African economy and its future socio-political stability, without the creation of new businesses South Africa faces challenges of economic stagnation. Therefore, the important role and positive contribution of entrepreneurship and the promotion of entrepreneurial culture in educational, economic and social development in South Africa cannot be overlooked. This paper seeks to answer pertinent questions that relate to entrepreneurship. Why is entrepreneurship necessary for economic development? What can government do to promote entrepreneurship amongst South African youth? How can universities inculcate a culture of entrepreneurship within their students? Can entrepreneurship be promoted by including it in programme design and curriculum within universities? The answers to these questions and their implications to high youth unemployment and entrepreneurship development are discussed in this paper.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Entrepreneurship; Government; Unemployment; Entrepreneurship development; Entrepreneurship -- South Africa; Unemployment -- South Africa; Universities and colleges -- South Africa; Education, Higher -- South Africa